Exploration of recovery of people living with severe mental illness (SMI) in low/middle-income countries (LMICs): A scoping review - Gamieldien, F.; Galvaan, R.; Myers-Franchi, Bronwyn; Syed, Z.; Sorsdahl, K. (BMJ PUBLISHING GROUP, 2021)
Objective: To examine the literature on how recovery of people with severe mental illness (SMI) is conceptualised in low/middle-income countries (LMICs), and in particular what factors are thought to facilitate recovery.